Pengaruh Motivasi Terhadap Keputusan Berkunjung Di Museum Joang 45 Jakarta - Saragi, Charles Parnauli; Hidayat, Ika Yulianti; Yuwantiningrum, Sri Endah (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Motivation can trigger the travel process. Tourist motivation is an important factor in carrying out an activity, starting or planning it. Therefore, it is important to know the motivation of tourists to visit tourist attractions, so that it can make it easier for tourist attraction managers to understand the desires and needs of tourists. The aim of this research was to determine the influence of motivation on the decision to visit the Joang 45 Museum, Jakarta. The tourist motivations examined in this research are physical motivation, cultural motivation, individual motivation, and status and prestige motivation. This research uses quantitative methods with a sample of 100 respondents. The sampling technique uses accidental sampling technique. Meanwhile, the data analysis techniques used are validity test, reliability test, normality test, simple linear regression, t test, and coefficient determination. Based on the analysis results from the t test, it shows that motivation which includes physical motivation, cultural motivation, individual motivation, as well as prestige and status motivation influences the decision to visit the Joang 45 Museum, Jakarta. Keywords: Tourist Motivation, Visiting Decisions, Museum